An analysis on the suitability of selected newspaper material as a teaching resource in efl courses. - Sánchez, Carmen (2010)
The purpose of this research work is to investigate the suitability of using selected newspaper material as a teaching resource in EFL courses. It is well known that people have different learning aptitudes, and one of them is the visual, that is why using reading material as newspaper articles, can help us as teachers to create interesting classes, enhancing in the students their capability to learn. In fact the use of selected newspaper material can be very effective to facilitate the learning process, motivating students to learn in a meaningful way by showing them the real life language and its importance.